Amazing Things Will Happen - Chapman, C. C., 1973- (Tantor Media, Inc., 2020)
Amazing Things Will Happen offers straightforward advice that can be put into action to improve your life. Through personal anecdotes from the author's life and interviews of successful individuals across industries, the book demonstrates how to achieve success, in all aspects of life, through hard work and acts of kindness. The book is split into five sections that detail how to begin the self-improvement journey. These sections include Taking a look at where you are now, how to cope with the situation you are currently in, and how to make the most of it until you can break free Exercises and practices that can help define your goals and how to set realistic tasks to reach them How to navigate the seas of doubters and obstacles to get to where you want to be How to make sure to enjoy the fruits of your labors How to ensure that you help others, once you have reached your goals Each of us has different goals in life, but everyone wants to succeed. Amazing Things Will Happen shows how to get on the path to success.